2018
DOI: 10.1111/hir.12224
|View full text |Cite
|
Sign up to set email alerts
|

Controlled before‐after study to evaluate change in evidence‐based practice of speech and language therapy students

Abstract: Trained students improved their EBP competencies. Nevertheless, the module could be strengthened along with better integration of EBP into clinical modules and across the curriculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 28 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…Durieux et al. (2018) recommend anchoring knowledge in concrete work situations in small groups of students; Klee et al. (2009) suggest basing courses on case studies in order to experiment with the search for concrete solutions; and Aglen (2016) notes the value of a problem‐based learning approach to brainstorm on practical cases that can be very effective, especially if there is a tutoring system with supervisors that give students maximum feedback (Goldstein, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Durieux et al. (2018) recommend anchoring knowledge in concrete work situations in small groups of students; Klee et al. (2009) suggest basing courses on case studies in order to experiment with the search for concrete solutions; and Aglen (2016) notes the value of a problem‐based learning approach to brainstorm on practical cases that can be very effective, especially if there is a tutoring system with supervisors that give students maximum feedback (Goldstein, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Reviewers independently evaluated the level of evidence and the quality of each publication using the Oxford Centre for Evidence-Based Medicine: level of evidence (OCEBM). 23 Discrepancies between the reviewers were addressed by a third author.…”
Section: Methodsmentioning
confidence: 99%
“…The topic of Evidence‐Based Practice is explored in three articles in this virtual issue. Durieux, Maillart, Donneau and Pasleau () carried out a before/after study to evaluate whether an educational module for undergraduate speech and language therapy students led to an improvement in their evidence‐based practice. The results showed that those students who received training showed an improvement in some EBP competencies.…”
Section: Evidence‐based Practicementioning
confidence: 99%